Diabetes Technology Meeting 2021. (July 2022) - Xu, Nicole Y.; Nguyen, Kevin T.; DuBord, Ashley Y.; Pickup, John; Sherr, Jennifer L.; Teymourian, Hazhir; Cengiz, Eda; Ginsberg, Barry H.; Cobelli, Claudio; Ahn, David; Bellazzi, Riccardo; Bequette, B. Wayne; et al.
Diabetes Technology Society hosted its annual Diabetes Technology Meeting on November 4 to November 6, 2021. This meeting brought together speakers to discuss various developments within the field of diabetes technology. Meeting topics included blood glucose monitoring, continuous glucose monitoring, novel sensors, direct-to-consumer telehealth, metrics for glycemia, software for diabetes, regulation of diabetes technology, diabetes data science, artificial pancreas, novel insulins, insulin delivery, skin trauma, metabesity, precision diabetes, diversity in diabetes technology, use of diabetes technology in pregnancy, and green diabetes. A live demonstration on a mobile app to monitor diabetic foot wounds was presented.